2007
DOI: 10.1172/jci31680
|View full text |Cite
|
Sign up to set email alerts
|

Impaired basolateral sorting of pro-EGF causes isolated recessive renal hypomagnesemia

Abstract: Primary hypomagnesemia constitutes a rare heterogeneous group of disorders characterized by renal or intestinal magnesium (Mg 2+ ) wasting resulting in generally shared symptoms of Mg 2+ depletion, such as tetany and generalized convulsions, and often including associated disturbances in calcium excretion. However, most of the genes involved in the physiology of Mg 2+ handling are unknown. Through the discovery of a mutation in the EGF gene in isolated autosomal recessive renal hypomagnesemia, we have, for wha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
280
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 323 publications
(283 citation statements)
references
References 41 publications
2
280
1
Order By: Relevance
“…Lower but not significantly different values for Ca 2 þ were recorded: 0.26 ± 0.03 and 0.23±0.02 mM, respectively (data not shown). Next, we analyzed the EGF-mediated upregulation of TRPM6 outward currents as previously published by Groenestege et al 29 Treatment of TRPM6-expressing HEK293 cells with 10 nM EGF for 30 min at 37 1C produced a 1.5-fold increase in WT TRPM6 compared to 1.33-fold for Q 1663 R, which was not significantly different. …”
Section: Functional Characterization Of Trpm6 Mutantsmentioning
confidence: 99%
“…Lower but not significantly different values for Ca 2 þ were recorded: 0.26 ± 0.03 and 0.23±0.02 mM, respectively (data not shown). Next, we analyzed the EGF-mediated upregulation of TRPM6 outward currents as previously published by Groenestege et al 29 Treatment of TRPM6-expressing HEK293 cells with 10 nM EGF for 30 min at 37 1C produced a 1.5-fold increase in WT TRPM6 compared to 1.33-fold for Q 1663 R, which was not significantly different. …”
Section: Functional Characterization Of Trpm6 Mutantsmentioning
confidence: 99%
“…These ligands have distinct motifs that govern their basolateral sorting (6)(7)(8). Of clinical relevance is a germline mutation in the basolateral sorting motif of EGF in individuals with isolated renal hypomagnesemia (9). In this autosomal recessive disorder, loss of EGF delivery to the basolateral surface impairs EGFR activity in the distal convoluted tubules, which is required for efficient magnesium absorption.…”
mentioning
confidence: 99%
“…Mutations in TRPM6 lead to hypomagnesemia with secondary hypocalcemia (HSH) indicating that this channel is important for the maintenance of the Mg 2ϩ balance (6 -8). Previous studies demonstrated that expression of TRPM6 is regulated by dietary Mg 2ϩ and its channel activity is strongly inhibited by the intracellular Mg 2ϩ concentration ([Mg 2ϩ ] i ) (8,9). Generally, Mg 2ϩ -free solutions are used to measure the characteristic outwardly rectifying TRPM6 currents (8,10,11).…”
mentioning
confidence: 99%
“…A recent study reported that epidermal growth factor (EGF) acts as an autocrine/paracrine magnesiotropic hormone via stimulating its receptor on the basolateral membrane of DCT cells, thereby specifically increasing TRPM6 current (18). Further, Groenestege et al (9) demonstrated that the renal TRPM6 mRNA level in ovariectomized rats was significantly reduced, whereas 17␤-estradiol treatment normalized TRPM6 mRNA levels. Next to this classical transcriptional pathway, accumulating evidence suggests also rapid estrogen effects that occur within minutes via a non-transcriptional route (19 -22).…”
mentioning
confidence: 99%